1993
DOI: 10.1007/bf00838158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiological study of the peripheral nervous system in the elderly

Abstract: The effect of age on the peripheral nervous system was investigated by clinical examination and neurophysiological studies in 59 subjects aged 60-103 years and 23 young subjects. A full laboratory screen for factors which, though clinically silent, may constitute risk factors (RFs) for peripheral neuropathy was also performed in the elderly subjects. Our findings show that the presence of RFs affects exceptionally the electrophysiological parameters in a statistically significant way. The age-dependent changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 27 publications
7
54
4
Order By: Relevance
“…16 In our study, SNAP amplitudes of median, right ulnar and radial nerves were lower in the older age group as compared to the younger ones. 22 Fujimaki et al in their study also found the similar decrease in SNAP amplitude of the median, ulnar, superficial radial, superficial peroneal and sural nerves with advancing age. 5 This may be due to loss of large nerve fibers in older individuals.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…16 In our study, SNAP amplitudes of median, right ulnar and radial nerves were lower in the older age group as compared to the younger ones. 22 Fujimaki et al in their study also found the similar decrease in SNAP amplitude of the median, ulnar, superficial radial, superficial peroneal and sural nerves with advancing age. 5 This may be due to loss of large nerve fibers in older individuals.…”
Section: Discussionmentioning
confidence: 54%
“…10 Also, in our study smaller CMAP amplitude was significantly related to advancing age. 22 Kurokawa et al in their study found lower CMAP amplitude in the older age as compared to the younger ones, 11 however, the CMAP duration did not differ among the two age groups. In contrast to their study, our study showed statistically significant effect of age on CMAP duration.…”
Section: Discussionmentioning
confidence: 83%
“…Most common was a reduced/absent ankle jerk (67%) followed by muscle weakness (55%) and reduced pinprick sensation (52%). However, similar abnormal leg neurological findings may be encountered in asymptomatic elderly people without reflecting pathology [22]. Hence, clinical findings on the whole are not specifically diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…To identify how these degenerative changes occur, several studies of human and rodent have compared electrophysiological and anatomical properties of young and aged neurons, peripheral nerves and target tissues. In humans, electrophysiological measures have found lower nerve conduction velocity in older individuals, suggesting impairment in axon structure and function [9,37]. Analysis of nerve fibers in aging mice from 20 months of age onward, showed both myelinated and unmyelinated fibers to be reduced in number, which in the very old mouse (33 months) approaches 50% loss [13].…”
Section: Introductionmentioning
confidence: 99%